Dipole-Switchable poly(para-phenyleneethynylene)s: ferroelectric conjugated polymers - Kushida, Soh; Smarsly, Emanuel; Bojanowski, Maximilian; Wacker, Irene; Schröder, Rasmus R.; Oki, Osamu; Yamamoto, Yohei; Melzer, Christian; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2018)
Dipolar 2,3-difluorobenzene units are introduced into the backbone of a poly(para-phenyleneethynylene) (PPE) to generate a ferroelectric conjugated polymer. The structural features of the partially fluorinated PPE allow for the generation of a remanent polarization in the solid state; the difluorinated benzene rings behave as molecular rotors at high temperature, while at room temperature, stacking of such rings clamps down the ring orientation. The molecular dipoles can still be oriented by moderate external electrical fields at room temperature, and this PPE is then ferroelectric. The concept should be transferable to other poly(aryleneethynylene)s, and novel conjugated ferroelectric conjugated polymers will be accessible using this concept.